Analisis Pengambilan Keputusan Untuk Korelasi Pembelian Produk Menggunakan Metode Association Rules - Khrisnawati, Erlin Ayu; Renita, Dayu (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2023)
Business people are required to be able to keep up with the increasingly dynamic times. Business people must have the right strategy to be able to compete with competitors so that the business they run continues to generate profits. From the existing sales transaction data, it can be used for decision making for business people in developing a good strategy in developing their business. By using data mining with the Association Rules method can be used to analyze existing sales patterns. In this test, the author uses the Apriori Algorithm to analyze the market basket analysis to find out the correlation between product purchases and products that are often purchased by consumers. From the analysis of the a priori algorithm, it produces frequent items that meet the minimum values ??of support and confidence. The result of this test is to provide product recommendations to consumers based on interrelated items and as a reference in product promotion to support decisions in developing good strategies in their business.